Tight coupling between photosynthesis and soil carbon turnover indicative of rhizosphere priming in the field - McCloskey, Chris; Kirk, Guy J. D.; Otten, Wilfred; Paterson, Eric (EGU: European Geophysical Union, 2022)
While rhizosphere priming effects are well-documented under laboratory and controlled-environment conditions, their significance in undisturbed systems under field conditions is less clear. This is in part because it is impracticable to measure rates of rhizodeposition in the field with high resolution over a substantial period. We propose that photosynthesis, closely linked to rhizodeposition, can be used as a proxy for plant root activity.
Abstract only